Athlete and coach’s perspectives on sports nutritionists’ role in enhancing sports performance in Indonesia Sports Training Centers - Mirza Hapsari Sakti Titis Penggalih; Laksono Trisnantoro; Zaenal Muttaqien Sofro; Mustika Cahya Nirmala Dewinta; Naila Alfi Syarifah; Kurnia Mar'atus Solichah (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2023)
The role of a nutritionist as a sportsman was a legal mandate listed on Law No. 3 of 2005 in Article 63 concerning the National Sports System, stated that nutritionists are one of the sports personnel. However, the implementation of the nutritionist's role in the athlete training center was still lacking. The importance of nutritionist existence ought to be assessed to explore the perception of athletes and coaches. Qualitative approach was used to analyze focus group discussions on 15 athletes and 10 coaches located in 3 cities in Indonesia (Jakarta, Yogyakarta, Malang). Results, the acceptance of the food in the training center are satisfactory even though some still eat out. More knowledge concerning nutrition, performance, and posture are obtained from in-class education, brochure, personal counselling, and small talk by the presence of nutritionists. Conclusion, athletes and coaches perceive that nutritionists are urgently necessary for optimum nutrition support to enhance sports performance.